POST-CERTIFICATION GOVERNANCE: AN EXAMINATION OF INSPECTORIAL OVERSIGHT AND BUSINESS COMMITMENT IN ACEH’S HALAL REGULATORY FRAMEWORK - Vira Yuniar; Irwansyah; Muhammad Iqbal (JURISTA: Jurnal Hukum dan Keadilan, 2026)
This study examines the effectiveness of the LPPOM MPU Aceh supervision system in ensuring business operators’ post-certification commitment to halal certification. The background to the research is the phenomenon of inconsistent compliance by business operators with halal standards, as revealed by the 2023 inspection, which found that 26.4% of 87 businesses in Banda Aceh did not meet halal standards despite holding valid certificates. This study employs a descriptive qualitative approach, combining primary data from in-depth interviews with LPPOM MPU Aceh officials, halal auditors, and business operators, alongside secondary data from supervision reports and relevant regulations. The research findings indicate that LPPOM MPU Aceh implements a multi-layered supervision mechanism through routine and unannounced inspections, with 39 auditors overseeing 900–1,000 business units. Practices on the ground face complex challenges, including a limited auditor-to-business operator ratio (1:23–26), a lack of operational funding, and a gap in business operators’ understanding of the principles of the Halal Assurance System (SJPH), which reduces the effectiveness of supervision by 20–30% with coverage of only 60–70% of priority targets. Violations identified include the use of non-certified ingredients, cross-contamination, and non-compliance with product composition requirements. This study concludes that although the supervision system based on Aceh Qanun No. 8 of 2016 has served as a structured compliance framework, its effectiveness requires improvement through digital transformation grounded in risk management, institutional capacity building, and the development of a more adaptive supervision model tailored to SME characteristics.